Design, synthesis, and antitumor activity of PLGA nanoparticles incorporating a discovered benzimidazole derivative as EZH2 inhibitor. (1st August 2021) - Elkot, Hoda A.; Ragab, Ibrahim; Saleh, Noha M.; Amin, Mohamed N.; Al-Rashood, Sara T.; El-Messery, Shahenda M.; Hassan, Ghada S.
Abstract: Purpose: Targeting enhancer of zeste homolog 2 (EZH2) can represent a hopeful strategy for oncotherapy. Also, the use of PLGA-based nanoparticles as a novel and rate-controlling carrier system was of our concern. Methods: Benzimidazole derivatives were synthesized, and their structures were clarified. In vitro antitumor activity was evaluated. Then, a modeling study was performed to investigate the ability of the most active compounds to recognize EZH2 active sites. Compound 30 (Drug) was selected to conduct pre-formulation studies and then it was incorporated into polymeric PLGA nanoparticles (NPs). NPs were then fully characterized to select an optimized formula (NP4 ) that subjected to further evaluation regarding antitumor activity and protein expression levels of EZH2 and EpCAM. Results: The results showed the antitumor activity of some synthesized derivatives. Docking outcomes demonstrated that Compound 30 was able to identify EZH2 active sites. NP4 exhibited promising findings and proved to keep the antitumor activity of Compound 30 . HEPG-2 was the most sensitive for both Drug and NP4 . Protein analysis indicated that Drug and NP4 had targeted EZH2 and the downstream signaling pathway leading to the decline of EpCAM expression. Conclusions: Targeting EZH2 by Compound 30 has potential use in the treatment of cancer especially hepatocellular carcinoma. Graphical abstract: Image 1 Highlights: Compound 30 "Drug" had a promising antitumor activity. Drug-loaded polymeric nanoparticles kept the antitumor activity of the drug. The drug in its pure and nanoform had targeted EZH2 and EpCAM expression. Compound 30 can have a prospective role in the treatment of liver cancer.